Computer Networks and E-Commerce - Diwan, Parag; Singh, Dharm Bir (New Delhi Pentagon Press, 2000)
The book is written for managers who are planning to use networking, internet and E-commerce technologies for providing secure and effective methods. The main feature of the book is that real life causes and group projects have been presented in a succinc
Keywords: Computer networks; Electronic commerce; Commerce